Influence of household finance on stability of public finances - Лєщина, Ю. В.; Хмелькова, І. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The relevance of the study is determined by theoretical definition of the essence and specification of the components of the subsystems of public finances, which allowed us reveal the need for studying the role of household finance in public finances, which have a direct connection with the state budget, local budgets and funds of social importance. As a subject of public finance, households, through participation in the formation and use of public finance, can influence the stability of this category. Analysing profitable part of the state budget,  namely stake of payments from the profits of householders in a budget, and considering their personal interest in a social sphere, it was their public interest that unites interests of the state and private is certain. Due to the fact that almost a third of the expenditures of the consolidated budget is allocated for social protection and security, and one of the public finance subsystems is fully owned by non-state social funds, financial flows that are defined and guaranteed by the state for all citizens and personify public interests were considered. The analysis of the expenditures of the state and local budgets determined that the expenses on the social protection of pensioners and the social protection of the family, children and young people are of the greatest interest, and they are directly related to the finances of households. Using the indicator of the stability of public finances, articles on social protection were examined, and it was determined which areas could adversely affect the sustainability of public finances. Social protection of the retired people refers to the area with a negative impact on public finances. The obtained results require further studies of the relationship of the social sphere with household finance, which will make it possible to determine the instruments of influence and regulation in the sphere of public finances.